Defining the Content of an Opportunistic Osteoarthritis Consultation With Primary Health Care Professionals: A Delphi Consensus Study. Issue 6 (30th May 2013) - Finney, Andrew; Porcheret, Mark; Grime, Janet; Jordan, Kelvin P.; Handy, June; Healey, Emma; Ryan, Sarah; Jester, Rebecca; Dziedzic, Krysia
<x xml:space="preserve">Abstract</x> Objective To define the core content for an opportunistic consultation between a health care professional (HCP) and a patient with osteoarthritis (OA) in primary care. Methods An ideas generation round and a 2‐round Delphi postal consensus study allowed participants to rank the importance of tasks for an opportunistic consultation. The study was conducted with a lay group (n = 18) and 3 groups of HCPs (n = 30 for general practitioners, n = 19 for practice nurses, and n = 37 for allied health professionals). Results The ideas generation round formulated 35 consultation tasks. There was a 50% response rate to the 2‐round postal exercise (n = 52). Consensus was reached on 12 tasks for an opportunistic OA consultation using a >80% level of agreement across all groups. Three of these consultation tasks were defined at 100%. The 3 tasks were questions asked by the HCP about how things are going with the condition, the type and amount of pain the patient has, and whether the patient is taking regular analgesia. Conclusion In a Delphi study to define the content of an opportunistic primary care OA consultation, 12 consultation tasks provided the content of a comprehensive consultation. Three of these tasks with 100% agreement could be adopted in any multidisciplinary consultation for OA in primary care. Inquiring about the condition, the type and amount of pain the patient has, and whether analgesia is being taken forms a core set of questions that are considered important by both lay and health professional groups in an opportunistic consultation.